IBM PENGUATAN DAYA SAING BERKELANJUTAN PADA KELOMPOK BUDIDAYA IKAN LELE DI PUGER -JEMBER - Diana Dwi Astuti; Tamriatin Hidayah; Hamzah Fansuri (STIE Mandala Jember, 2013)
Science and technology for the Community (Iptek bagi Masyarakat/IbM) can be used as a vehicle in community service activities to actively improve the efficiency and productivity of businesses partners, and is the application of science and technology by implementing and lecturers can provide experiences for students that entrepreneurship has the insight and knowledge in order to foster the entrepreneurial spirit. Implementation of the activities carried out through the joint identification of problems between partners, implementing faculty and students. Based on the problems identified priority considering it is made in time and cost. The conclusion that can be drawn from the implementation of IBM, is the presence of unresolved issues due to time constraints and the cost of production lay out, while've accomplished is making catfish feed (pellets), diversification of processed catfish (shredded, chips, nuggets), support tools (tool maker catfish feed / pellets, presto, pans, pots, tools shredded pres, pres plastic tool, blender), catfish care, and managerial aspects. The need for these activities to be continued in order to provide more benefits for partners mainly because, the desire to continue this activity is the input from partners and as also suggested by the reviewer as business partners to conduct monitoring in Jember.